Pengembangan E-Modul pembelajaran Menulis Teks Laporan Hasil Observasi berbasis inquiry learning Siswa Kelas VII - Idrus Idrus; Nurmaya Medopa; Diana Sartika; Mas’ud Muhammadiah; Muh. Safar; Everhard Markiano Solissa (Departement of Mathematics Education, 2023)
This type of research is research and development. The development model in this research is the 4-D model which consists of four development stages, namely define, design, develop, and disseminate. The test subjects of this module were seventh grade students of MTs Al Khairaat Tavanjuka. This research was limited to MTs that have used the revised edition of the 2013 curriculum. The school is MTs Alkhairaat Tavanjuka. The data obtained from the trial were in the form of qualitative and quantitative data. The instruments used to collect data were validated by experts who understood them first. The instruments used consisted of interview sheets, student analysis questionnaires, curriculum analysis questionnaires, concept analysis questionnaires, product validation sheets, e-module practicality sheets, student activity observation sheets, writing performance tests, writing performance test assessment rubrics, and e-module distribution questionnaires. The e-module development process that has been carried out includes four stages, namely defining, designing, developing, and disseminating. The development process produced a product in the form of e-modules for learning to write inquiry learning-based observation report texts that are valid, practical, and effective. The feasibility aspects of content, language, presentation, and graphics can be reviewed from the validity of this learning e-module with an e-module validity value of 94.62 with a very valid category.